2013
DOI: 10.1039/c3ob41728j
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the synthesis of a novel, anti-HIV active integrase inhibitor

Abstract: The novel HIV-1 integrase inhibitor 1, discovered in our laboratory, exhibits potent anti-HIV activity against a diverse set of HIV-1 isolates and also against HIV-2 and SIV. In addition, this compound displays low cellular cytotoxicity and possesses a favorable in vitro drug interaction profile with respect to isozymes of cytochrome P450 (CYP) and uridine 5'-diphospho-glucuronosyltransferase (UGT). However, the total synthesis of this significant HIV integrase inhibitor has not been reported. This contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Nair et al reported on the discovery of a novel anti-HIV active INI possessing low toxicity and inhibition EC 50 value of 19-35 nM depending on the HIV subtype [14,15]. The multistep synthesis (Scheme 2) started with readily available pyridine and benzene derivatives and comprised lithiation of 5-bromo-2-methoxypyridine (4) followed by reaction with 2,6-difluorobenzaldehyde.…”
Section: Monocyclic Pyridinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nair et al reported on the discovery of a novel anti-HIV active INI possessing low toxicity and inhibition EC 50 value of 19-35 nM depending on the HIV subtype [14,15]. The multistep synthesis (Scheme 2) started with readily available pyridine and benzene derivatives and comprised lithiation of 5-bromo-2-methoxypyridine (4) followed by reaction with 2,6-difluorobenzaldehyde.…”
Section: Monocyclic Pyridinesmentioning
confidence: 99%
“…Reactions of the latter with alkoxyaminopyridines 21 in the presence of EDC hydrochloride and 1-hydroxy-7-azabenzotriazole Dual inhibitors of HIV reverse transcriptase and integrase were synthesized on the basis of pyridine-containing reverse transcriptase inhibitor Delavirdine [19]. The synthesis was accomplished starting with reactions of diversely substituted acetylindole-2-carboxylic acids 13 and 3-isopropylamino-2-(piperazyn-1-yl)-pyridine (14) in the presence of carbonyl diimidazole (CDI) to give corresponding amides 15 (Scheme 4). Further reactions with diethyl oxalate and basic hydrolysis of the esters 16 afforded target 2,4-diketoacids 17.…”
Section: Monocyclic Pyridinesmentioning
confidence: 99%
“…Integrase inhibitor 1 (left) and its X-ray crystallographic structure (right) depicting its preferred tautomeric form, conformation and intramolecular hydrogen bonding (Bacsa et al, 2013; Okello et al, 2013b). …”
Section: Figmentioning
confidence: 99%
“…Synthesis of the precursor 8 from commercially available 5-bromo-2-methoxypyridine ( 3 ) involved the following steps: in situ generated aromatic nucleophile addition to aldehyde; demethylation/deoxygenation; radical bromination; benzylation; palladium-catalyzed cross-coupling; Claisen condensation; and acid or base-catalyzed hydrolysis. 24 Yields for the individual steps are indicated in brackets in Scheme 1. Compound 2 was produced in >99.8% purity.…”
mentioning
confidence: 99%